EFEKTIVITAS LARUTAN EKSTRAK JERUK NIPIS (Citrus Aurantifolia) SEBAGAI OBAT KUMUR TERHADAP PENURUNAN INDEKS PLAK PADA REMAJA USIA 12-15 TAHUN - Studi di SMP Nurul Islami, Mijen, Semarang - Rr. Sarah Ladytama; Arlina Nurhapsari; Moh. Baehaqi (Odonto : Dental Journal, 2014)
Background: Plaque is formed by colonizing bacteria that adhere on the surface of teeth can be caused dental and oral disease. Using mouthwash can prevent plaque formation quickly and easily. Lime can be used as alternative herbal mouthwash to decrease plaque index because of antibacterial content. The purposed of this study is to determined the effectiveness of lime with concentration of 20%,40% and 60% as mouthwash in the term of plaque index decrease at teens 12-15 years old. Method: This study was an quasi experimental using post test only control group design method which is perform to 12 students who at teens 12-15 years old at Nurul Islami Secondary High School, Mijen-Semarang using until four weeks. The sample were given lime extract with many concentration every weeks. Dental plaque score was measured before and after intervention. The data analyzed with Kruskal–Wallis and Mann-Whitney test. Result: Result showed that lime extract with many concentration effective to decrease dental plaque index. Kruskall-Wallis test and Mann-Whitney test showed significance value 0,000 (p<0,05), there are significant differences among concentration. Conclusion: It is concluded from this research that the higher level of lime extract concentration increasing flavonoid content. There are significant differences of lime extract with 20%, 40%, 60% concentration as mouthwash in decreasing plaque index. The highest decrease plaque happen in concentration 60%.